The Effect of Financial Risks Related to the Industrial Sector and Macroeconomic Factors on the Financial Stability of Commercial Banks in Indonesia - Khaerunissa, Dinda; Vivian, Vivian; Lestari, Henny Setyo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study uses panel data regression, a two-step dynamic approach, to examine the effect of industry-specific financial risk and macroeconomics on the financial stability of private commercial banks in Indonesia. This study offers a comprehensive evaluation of how various elements affect financial stability over a 5-year period by examining data from 43 conventional banks. The results show that the financial stability of several banks has a positive effect on the variables of previous year stability, credit risk, liquidity, and bank concentration, a negative effect on the variables of bank size and gross domestic product, and no effect on the variable of real interest rate. On the other hand, lower financial stability is associated with larger banks and a country's economic performance. Larger banks may face greater operational and risk management difficulties, and financial stability may be disrupted by the real interest rate. Policy makers and bank managers, who face difficulties in controlling credit risk and bank size, need to understand these insights. According to the study, resilience can be strengthened by previous financial stability and positive economic indicators, but to maintain financial stability, it is necessary to pay attention to reducing the risks associated with large banks and credit risk to ensure sustainable financial stability.